2000
DOI: 10.1046/j.1439-0329.2000.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between presence of basidiomes, above‐ground symptoms and root infection by Collybia fusipes in oaks

Abstract: Summary Collybia fusipes is a common cause of root rot on oak in the north of France. Collybia fusipes basidiomes can be as frequent on oaks in stands where no decline of the trees occurs compared with stands where the decline is chronic. This might be explained by differences in the amount of roots damaged by the parasite. To test that hypothesis, 430 oak trees, Quercus petraea, Quercus robur and Quercus rubra, located in six forests were selected. Half of them showed C. fusipes basidiomes at the trunk base.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 6 publications
2
21
0
Order By: Relevance
“…did not appear to have a consistent relationship with oak crown health status. The correlation between crown health status and damages induced by C. fusipes confirmed that severe infections of this pathogen is linked to decline [26] and shows additionally that in the studied plots, most of the decline is linked to C. fusipes infection. Thereafter, it is not surprising to find several mentions of C. fusipes in association with different decline episodes [11,15].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…did not appear to have a consistent relationship with oak crown health status. The correlation between crown health status and damages induced by C. fusipes confirmed that severe infections of this pathogen is linked to decline [26] and shows additionally that in the studied plots, most of the decline is linked to C. fusipes infection. Thereafter, it is not surprising to find several mentions of C. fusipes in association with different decline episodes [11,15].…”
Section: Discussionsupporting
confidence: 67%
“…In pedunculate oaks, hypertrophy of the bark is usually observed as infected bark is thickened up to 3-4 cm. Previous work showed that C. fusipes is consistently isolated from such lesions on oak roots [15,25,26]. The infection status of each major root was assessed within the following four classes: (0) no necrosis detected; (1) superficial necrosis present, but covering less than half of the root circumference (penetration of C. fusipes in the bark of no more than 1-2 mm); (2) necrosis covering one side of the root entirely with a penetration of the parasite in the bark usually more than 2-5 mm; (3) C. fusipes infection over the entire root circumference but root still alive (penetration of the parasite in the bark of usually more than 4-5 mm); (4) root dead with decayed wood.…”
Section: Assessment Of Root Damage Induced By C Fusipesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, efforts to demonstrate that oak trees growing in sandy soils or subjected to water shortage were more susceptible to C. fusipes were not successful [35,37]. Furthermore, it was demonstrated that, at a given level of root destruction by C. fusipes, the likelihood of decline of a tree was greater in a sandy loam compared to a clay loam [36,126]. This could be explained by a decreased ability of root-damaged trees to cope with situations of poor water availability.…”
Section: Possible Role Of Root Pathogens In Declines Associated With mentioning
confidence: 99%
“…The interaction between insect defoliation and powdery mildew has been less frequently invoked to explain more recent oak declines (but see Selochnik et al 1994, Thomas et al 2002, Petercord 2011) while other inciting factors, especially drought and root pathogens have been put forward (Landmann et al 1993;Brasier et al 1993;Jung et al 2000;Marçais et al 2000). However, insect defoliations remain very important causes of oak decline (Landmann et al 1993, Thomas et al 2002 and Gerard et al 2013 showed that very severe powdery mildew infection were common after insect defoliations.…”
Section: Powdery Mildew As a Contributing Factor Of Oak Decline Espementioning
confidence: 99%